Bilateral Adie’s Pupil following Laser Treatment of the Ischemic Peripheral Retina for Uveitis: A Case Report - Satoko Akahane (Karger Publishers, 2021)
Adie’s pupil is a neurological condition of unknown origin with unusual, asymmetric presentation known as anisocoria with the enlarged pupil failing to react to light. It is believed that this pupillary abnormality results from damage to the ciliary ganglion or postganglionic short ciliary nerves. Affected individuals (usually female) may be symptomatic with photophobia or difficulty reading in the diseased eye. Although most Adie’s pupil cases are idiopathic, previous studies have associated photocoagulation and uveitis with symptom onset. To the best of our knowledge, there have been no reports of specific means of preventing Adie’s pupil. We describe a patient who experienced varying severities of Adie’s pupil after separate laser treatments of the ischemic peripheral retina for uveitis. Fluorescein angiography revealed peripheral retinal nonperfusion in the bilateral eyes of a 37-year-old Japanese female who had been suffering from posterior uveitis. To avoid proliferative changes, 360° laser photocoagulation of the retinal nonperfusion region located in the far periphery was first delivered to the left eye over 2 sessions. Soon after treatment, the patient complained of acute photophobia and blurred vision in the treated eye. Ocular examination revealed left pupil dilation and poor light sensitivity, although the pupil was reactive to a close stimulus. The left pupil also displayed positive denervation sensitivity based on the dilute pilocarpine (0.125%) test. Adie’s pupil was diagnosed based on these observations. Three months later, similar, albeit milder, findings were observed in her right eye after 360° peripheral laser photocoagulation that was more conservatively performed over 4 sessions. Four months after the first treatment, her subjective visual function had improved, and the pupil diameter had decreased to a normal size in both eyes without additional treatment. We encountered a patient whose severity of Adie’s pupil was apparently reduced by more conservative laser photocoagulation of the ischemic peripheral retina.